APLIKASI SISTEM CONTROL FEEDBACK KUALITAS FITTING FUNCTION DAN APPEARANCE BERBASIS WEB DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA PT XYZ - Ezra Nugroho; Muhammad rifqi (Sekolah Tinggi Teknik - PLN, 2019)
At this time the development of technology in helping and making it easier for the company so much feelt, one of them is XYZ Company who use the whatsapp application as an medium information for conveying problem to the PIC. Like a quality problem Fitting, Function and Apearence, this application can only convey problem information in the form of text and images, data input is still manual and for decision making problem solving priority is still manual based on the user, other than that the data is stored by external, so that confidentiality and security data can not be guaranteed and there are also difficulties when we want to find data that has been informed. So that we need feedback system application that can give decisions on problem solving priorities, in this application using the web and using the Simple Additive Weighting (SAW) method, in this SAW method to determine problem solving priorities using the sum of the weight values of the parameter level problem and quantity of problems, so that in the solving problems can be in accordance with the importance of the problem to be resolved immediately.